Literasi dan Sistem Pembelajaran Daring Penunjang Kualitas Belajar Mengajar Sekolah Dasar Inklusi - Dian Rahmani Putri; Dermawan Waruwu; Gede Suardika (Jurnal Surya Masyarakat, 2023)
This Community Partnership Program (PKM) answers the problems faced by partner, SDN 2 Inclusion in Bengkala Buleleng Village, Bali. The first problem is the lack of literacy that meets the needs of the Inclusive Elementary School. The second problem there is no online learning system. Moreover, the third, teachers do not have facilities of the literacy and learning system for the inclusive elementary school. The solutions offered to answer the three problems are, first, literacy that supports learning needs. Second, the provision of an integrated website-based learning information system and library-based teaching materials library service. Third, literacy for teachers about the application of learning systems and the manufacture of teaching materials that facilitate the teaching and learning process. The method of implementing this PKM is community participation by developing into a number of activities such as: participatory mentoring, workshops, simulations and substitution of science and technology, creation of learning information systems and library services for integrated web-based teaching materials as well as literacy and socialization processes. The evaluation of this activity uses the CIPP method, namely context, input, process, and product tailored to the needs of literacy and teaching and learning processes. The target of this program is the availability of online learning support facilities, increasing the ability of teaching teachers in online teaching and creating digital learning media, as well as the availability of a Learning System and Teaching Material Library Service.